Personalized Automation of Treatment Planning for Linac-Based Stereotactic Body Radiotherapy of Spine Cancer - Cilla, Savino; Cellini, Francesco; Romano, Carmela; Macchia, Gabriella; Pezzulla, Donato; Viola, Pietro; Buwenge, Milly; Indovina, Luca; Valentini, Vincenzo; Morganti, Alessio G.; Deodato, Francesco (Frontiers in Oncology, 2022)
Purpose/Objective(s): Stereotactic ablative body radiotherapy for vertebral metastases is a challenging treatment process. . We performed a dosimetric evaluation of the new Pinnacle Personalized engine for full planning automation of SBRT spine treatments in terms of plan quality, treatment efficiency and delivery accuracy. Materials/Methods: Six patients with vertebral metastases were re-optimized using two different automated engines implemented in the Pinnacle3 TPS. These two automated engines, the currently used Autoplanning and the new Personalized are both template-based algorithms that use a wish-list to formulate the planning goals and an iterative approach able to mimic the planning procedure usually adopted by experienced planners. The boost tumor volume (BTV) was defined as the macroscopically visible lesion on RM examination and the planning target volume (PTV) corresponds with the entire vertebra. Dose was prescribed according to simultaneous integrated boost strategy with BTV and PTV irradiated simultaneously over 3 fractions with dose of 30 Gy and 21 Gy, respectively. Clinically accepted manually generated (MP) and automated plans generated with both Autoplanning (AP) and Personalized engines (Pers) were compared by dose-volume histogram metrics and conformity indexes. The planning efficiency and the accuracy of dose delivery were assessed for all plans. Results: For similar spinal cord sparing, automated plans reported a significant improvement of targets coverage and dose conformity. On average, Pers plans increased near-minimal dose D98% by 10.4% and 8.9% and target coverage D95% by 8.0% and by 4.6% for BTV and PTV, respectively. Automated plans provided significantly superior dose conformity and dose contrast by 37%-47% and by 4.6%-5.7% compared with manual plans Overall planning times were dramatically reduced to about 15 and 23 minutes for Pers and AP plans, respectively. The average beam-on times were found to be within 3 minutes for all plans. Despite the increased complexity, all plans passed the 2%/2 mm γ-analysis for dose verification. Conclusion: Automated planning for spine SBRT through the new Pinnacle Personalized engine provided an overall increase of plan quality in terms of dose conformity and a major increase in efficiency. In this complex anatomical site, Personalized strongly reduce the tradeoff between optimal accurate dosimetry and planning time.